Antioxidative effects of sulphurous water from Macerata Feltria Thermal resort in patients with osteoarthritis - benedetti, S.; Pagliari, S.; Benvenuti, F.; Marini, D.; Galli, T.; Oliva, F.; Lazzari, P.; Canestrari, F. (Progress in Nutrition, 2007)
It has been widely demonstrated that reactive oxygen species are implicated as the main causative factors of osteoarthritis (OA), a degenerative joint disease characterized by a progressive degradation of the articular cartilage. Sulphur thermal therapies are employed in the treatment of OA since ancient times; however, their mechanisms of action in the control of OA are only partially known. In the present study, we undertook a preliminary investigation aim at evaluating the antioxidative effects of a cycle of mud-therapy with sulphurous water in combination with hydropinotherapy in fifteen patients affected by degenerative OA from the Thermal Resort of Macerata Feltria. Subjects were evaluated both before (T0) and after (T1) therapy thus to monitor their antioxidant profile as well as some indices of oxidative damage. Interestingly, at the end of the thermal treatment we evidenced a significant increment of plasma total antioxidant capacity and total thiol levels, with a concomitant decrement of both lipid and protein oxidation markers. Our findings of improved body redox status in OA patients undergoing sulphur thermal therapy suggest major benefits from sulphurous water in reducing bio-molecule oxidation, possibly furnishing a valid protection against oxidative injury commonly associated with aging and age-related degenerative diseases.